SEKOLAH ALAM DI MAKASSAR DENGAN KONSEP ARSITEKTUR BERKELANJUTAN - Wahab, Abdul; Tauhid, Fahmyddin A'raaf; Arfan, Taufik (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2014)
Schools nature is a form of alternative education that uses nature as the main media as her students learning by using active or action learning where children learn through experience firsthand experience. The use of nature as a medium of learning is expected that in the future children or students more aware of the environment and know the application of knowledge learned, not only limited to theory. The design of this nature school also strengthened in view of Islam because it relates to science. In Islam has always emphasized learning activities and obligatory. Prompts Prophet, for every Muslim to seek knowledge should support the progressive development of human life, but within the limits of the pleasure of by Allah SWT. In addition, the most important thing of the study is how science is practiced for the good. digunskan concept in this design, combined with the study of literature and the state directly in the field and planned in the model concept and led to the idea of designing and developing desainnya. The results of the design adapted to local conditions acceptable to the environment and a recommendation for its development.